Age‐related changes in amygdala–frontal connectivity during emotional face processing from childhood into young adulthood. Issue 5 (2nd March 2016) - Wu, Minjie; Kujawa, Autumn; Lu, Lisa H.; Fitzgerald, Daniel A.; Klumpp, Heide; Fitzgerald, Kate D.; Monk, Christopher S.; Phan, K. Luan
Abstract: The ability to process and respond to emotional facial expressions is a critical skill for healthy social and emotional development. There has been growing interest in understanding the neural circuitry underlying development of emotional processing, with previous research implicating functional connectivity between amygdala and frontal regions. However, existing work has focused on threatening emotional faces, raising questions regarding the extent to which these developmental patterns are specific to threat or to emotional face processing more broadly. In the current study, we examined age‐related changes in brain activity and amygdala functional connectivity during an fMRI emotional face matching task (including angry, fearful, and happy faces) in 61 healthy subjects aged 7–25 years. We found age‐related decreases in ventral medial prefrontal cortex activity in response to happy faces but not to angry or fearful faces, and an age‐related change (shifting from positive to negative correlation) in amygdala–anterior cingulate cortex/medial prefrontal cortex (ACC/mPFC) functional connectivity to all emotional faces. Specifically, positive correlations between amygdala and ACC/mPFC in children changed to negative correlations in adults, which may suggest early emergence of bottom‐up amygdala excitatory signaling to ACC/mPFC in children and later development of top‐down inhibitory control of ACC/mPFC over amygdala in adults. Age‐related changes in amygdala–ACC/mPFC connectivity did not vary for processing of different facial emotions, suggesting changes in amygdala–ACC/mPFC connectivity may underlie development of broad emotional processing, rather than threat‐specific processing. Hum Brain Mapp 37:1684–1695, 2016 . ©2016 Wiley Periodicals, Inc .